Difficulty in the removal of epidural catheter for labor analgesia - Mohamed S Hajnour (Saudi Journal of Anaesthesia, 2017)
For labor pain management epidural analgesia is a popular and an effective method. Difficult removal of epidural catheters occasionally occurs, and several maneuvers have been recommended. The purpose of this article is to raise awareness of the problem of retained epidural catheter fragments and identify the potential impact of complications.